Pengaruh Variasi Jarak Pelat Helical Terhadap Daya Dukung Tarik Helical Pile Pada Tanah Gambut - Robi Handi Putra; Ferry Fatnanta; Muhardi Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Helical pile can provide an alternative for wood pile over peat soil. The reaserch studied about the effect of spacing of helical plates to uplift capacity of helical pile and compared to wood pile and helical without pile. The spacing of helical plates used were 20, 30, and 50 cm. Uplift iltimate capacity was interpreted by Tangent Intersection and Terzaghi and Peck method. Theoritical uplift capacity of helical pile was calculated using Iindividual Plate Bearing and Cylindrical Shear method. Based on the result, correlation of uplift capacity and spacing of helical plates was not linier proportional. Spacing of helical plates 30 cm showed the biggest capacity compared to space 20 and 50 cm. According to interpretation method, the uplift capacity of helical pile approach to Cylindrical Shear mechanism better than Individual Bearing. More over, helical pile had a greater uplift capacity compared to wood pile or helical without pile.Keywords: Helical Pile, Spacing of Helical Plates, Peat soil, uplift Capacity, Wood Pile, pile without helical.